2016
DOI: 10.1177/1073191115625800
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Eating Pattern Inventory for Children in a General Population Sample of 11- to 12-Year-Old Children

Abstract: Previous research suggests that the Eating Pattern Inventory for Children (EPI-C) is best conceptualized as comprising four factors: dietary restraint, emotional, external eating and parental pressure to eat. This study aims to examine the psychometric properties of the EPI-C and to test gender and weight group differences. The population-based study sample comprised 1,939 children aged 11 to 12 years from the Copenhagen Child Cohort (CCC2000). Psychometric properties were evaluated using multigroup categorica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Recently, we investigated the factor structure of the Danish version of the EPI-C [20] and found that the four-factor structure of the EPI-C originally proposed by Schacht et al [23] could be replicated in our sample. The internal consistency (Cronbach's alphas) for the present sample was .92, .87, and .73 for dietary restraint, emotional, and external eating, respectively.…”
Section: Outcome Measuresmentioning
confidence: 87%
See 2 more Smart Citations
“…Recently, we investigated the factor structure of the Danish version of the EPI-C [20] and found that the four-factor structure of the EPI-C originally proposed by Schacht et al [23] could be replicated in our sample. The internal consistency (Cronbach's alphas) for the present sample was .92, .87, and .73 for dietary restraint, emotional, and external eating, respectively.…”
Section: Outcome Measuresmentioning
confidence: 87%
“…Body mass index (BMI) was calculated based on objective measurements of height and weight at the 11-to 12-year follow-up as previously described [20]. The children were classified into BMI categories of underweight, normal weight, or overweight/obese using the age and gender-specific BMI cutoffs provided by the International Obesity Task Force [21,22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pupil distances ranging from 1 to 77 mm were divided into the high distance for >56 mm, normal for between 41 and 56 mm, and low distance for <41 mm. (Tables 3 & 4) show the mean and standard deviation (SD) values of students with scoliometer readings of >5° and ≤5°, respectively [17][18][19][20]. We found that students with scoliometer readings of > 5° had different vision in both left and right eyes.…”
Section: Study Participantsmentioning
confidence: 82%
“…7 More recently, the factorial structure and reliability have been established in a sample or preadolescents, with an explained variance of 64.8% and good internal consistency for three of the four of the EPI-C (Cronbach's α =0.73-0.92). 9 Children's eating attitudes test (ChEAT-26). 10 The Cheat-26 is a children's version of the eating attitude test (EAT).…”
Section: Instrumentsmentioning
confidence: 99%